Assessment of Factor VII Levels in Patients of Chronic Liver Disease - Nabeela Naeem , Muhammad Ayyub , Fazal-ur –Rehman (Journal of Rawalpindi Medical College, 2013)
Background : To determine the levels of coagulation factor VII in patients of chronic liver disease. Methods: In this descriptive study sixty known patients of chronic liver disease were included. Patients were stratified into three groups on the basis of Child-Pugh scoring system, utilizing ascites, bilirubin, albumin, prothrombin time and encephalopathy as markers of disease activity. The correlation of Child-Pugh scoring system with factor VII levels was analyzed Results: Majority ( 63.33%) were males . Mean age was 50.5 years. Majority of patients (82%) had deficient Factor VII levels. Factor VII levels revealed a declining trend from Child-Pugh class B to C. Conclusion: Due to its short half-life factor VII level can serve as a helpful marker in diagnosing the degree of liver damage and as a prognostic indicator during the course of treatment.